PENINGKATAN AKTIVITAS DAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPS DENGAN MODEL QUANTUM TEACHING DI KELAS IV SEKOLAH DASAR - Arwin Arwin (Universitas Negeri Padang, 2018)
The porpuse of this research was to describe the activity and learning result of social studies with quantum teaching model. This type of research is a classroom action research, which the stepon the class room research is the planning, implementation, observation and reflection. The research approach is qualitative research. Place of research at SD Pariaman city. Research subject is fourth elementary school, total students is 30. This research data collected by the instrument activity and learning result. Research shows, use quantum teaching model in learning social studies hearts can be improve the commercial article activities on students learning. The increase of social studies learning, show learners can work together with members of his group, created an atmosphere of fun, empowering and enabling the learners thinking ability, which in the end is geared towards the improvement of the capabilities and the results of learning social studies. The use of quantum teaching model is very effective to increase the activity and learning result of students.learning models quantum teaching, activity, study result